The Berlin Crisis of 1961 : Soviet-American Relations and the Struggle for Power in the Kremlin, June-November, 1961 - Slusser, Robert M. (Book collections on Project MUSE., 2019)
"The Berlin Wall (German: Berliner Mauer) was a barrier constructed by the German Democratic Republic (GDR, East Germany) starting on 13 August 1961, that completely cut off (by land) West Berlin from surrounding East Germany and from East Berlin. The barrier included guard towers placed along large concrete walls, which circumscribed a wide area (later known as the "death strip") that contained anti-vehicle trenches, "fakir beds" and other defenses. The Eastern Bloc claimed that the wall was erected to protect its population from fascist elements conspiring to prevent the "will of the people" in building a socialist state in East Germany. In practice, the Wall served to prevent the massive emigration and defection that marked Germany and the communist Eastern Bloc during the post-World War II period."--Wikipedia